Biological and chemical assessment of water hyacinth (Eichhornia crassipes (mart.) Solms.) of Phewa Lake, Nepal - Baral, Bikash; Vaidya, Geeta Shrestha (Scientific World, 2011)
Experiments relating to bioassay, phytochemical screening and bio-control of obnoxious aquatic weed i.e., water hyacinth were conducted in Nepal Academy of Science and Technology (NAST) laboratory. Bioassay was performed from the methanolic and aqueous extracts obtained by hot and cold percolation method that. The antibacterial and antifungal effects were performed against 11 clinical bacteria (2 gram positive and 9 gram negative) and 7 phytopathogenic fungi using agar well diffusion method. The pattern of inhibition varied with different extracts and the micro-organism tested. The soxhlet methanolic extract showed activity against 54.45% of bacteria and 57.14% fungi while cold methanolic extract showed activity against 45.45 % bacteria and 42.85% fungi employed. Similarly, hot aqueous extract showed activity against 18.18% bacteria and 42.85% fungi while in cold aqueous extraction, the activity was null and 57.14% against bacteria and fungi respectively. The methanolic fraction proved more effective than cold aqueous extract showing more antibacterial activity while cold aqueous extract showed comparably better result in different fungi employed. The most susceptible organisms were Klebsiella pneumoniae, Salmonella typhi, Sclerotium rolfsii, and Fusarium moniliforme. Preliminary phytochemical analysis of different extracts revealed the presence of alkaloids, reducing compounds, polyoses and saponins. The GC-MS analysis shows the presence of Phenols and Carotenoids as the bio-active compounds in the test plant. In regards to bio-control, the propagation of this weed was found to be totally checked within 21 days after the application of aqueous lechate of Lantana camara (1-3%), while that was checked within a month by the supplementation of young twigs powder of Ageratina adenophorum (7%). Key-words: Antimicrobial activity; Plant extract; ZOI; Phytochemicals; Biocontrol; GC-MS. DOI: http://dx.doi.org/10.3126/sw.v9i9.5520 SW 2011; 9(9): 57-62